Another approach you might take is to multiply the LHS by (a_1 +a_n)/2, keeping in mind that a_1 + a_n = a_2 + a_{n-1} = ... . Each term will simplify interestingly.
Dr Peterson's approach to multiply the LHS by (a_1 +a_n)/2, keeping in mind that a_1 + a_n = a_2 + a_{n-1} = helped me solving the problem. Thanks all for your help.
This site uses cookies to help personalise content, tailor your experience and to keep you logged in if you register.
By continuing to use this site, you are consenting to our use of cookies.